High brilliance γ-ray generation from the laser interaction in a carbon plasma channel - Heppe, Christian; Kumar, Naveen (Frontiers in Physics, 2022)
The generation of collimated, high brilliance γ-ray beams from a structured plasma channel target is studied by means of 2D PIC simulations. Simulation results reveal an optimum laser pulse pulse duration of 20 fs, for generating γ-photon beams of brilliances up to 10^20 s^-1mm^-1mrad^-2 (0.1 %BW)^-1 and photon energies well above 200 MeV in the interaction of an ultra-intense laser (incident laser power P_L ≥ 5 PW) with a high-Z carbon structured plasma target. These results are aimed at employing the upcoming laser facilities with multi-petawatt (PW) laser powers to study the laser-driven nonlinear quantum electrodynamics processes in an all-optical laboratory setup.